2016
DOI: 10.1007/s10616-016-9973-2
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic field controls cell cycle in cultured human glioblastoma cells

Abstract: Magnetic field has been widely used in clinical diagnostics or for clinical treatment and is an important biomedical technology. Glioblastoma multiforme U87 and U251 are models of a fast growing malignant cancer. We focused on cellular level drafting of these cell lines as a time-dependent effect indicator of static magnetic fields (2000 ± 600 Gauss) by using their fast-growing properties. Cell viability showed a significant decrease (p \ 0.01). The results coincided with the occurrence of apoptotic signals or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Our results demonstrated that SH-SY5Y cells exposed to SMS for 24 h show a decrease in cell viability immediately after the exposure (24 h). A previous study using glioblastoma cells submitted to SMS for 24 h corroborates these findings regarding cell viability (15). This effect on cell viability, however, was not long-lasting, since 24 h after exposure treated groups were not different from the control group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results demonstrated that SH-SY5Y cells exposed to SMS for 24 h show a decrease in cell viability immediately after the exposure (24 h). A previous study using glioblastoma cells submitted to SMS for 24 h corroborates these findings regarding cell viability (15). This effect on cell viability, however, was not long-lasting, since 24 h after exposure treated groups were not different from the control group.…”
Section: Discussionsupporting
confidence: 80%
“…Potential uses and effects of magnetic stimulation over cellular processes have been described, particularly using static magnetic stimulation (SMS). Apart from physiological and homeostatic events, such as wound healing (14), SMS has shown effects in cancer models of glioblastoma (15), adenocarcinoma (16) and leukemia (17), where it has been shown to control the cell cycle, reduce drug resistance to cisplatin and enhance natural killer cell cytotoxicity against tumor cells, respectively. SMS, unlike repetitive transcranial magnetic stimulation (rTMS) -in which changes in the magnetic field create an electric current through electromagnetic induction -does not induce electric currents; however, it has been shown to influence a variety of biological systems (18).…”
mentioning
confidence: 99%
“…A concomitant rearrangement of the actin cytoskeleton was additionally reported [149]. This raises the general question of to which extent cells can respond to forces generated from static magnetic fields [150][151][152]. In the context of dentistry, it needs to be considered that ferromagnetic compounds can sometimes be found as part of a prosthetic material [153,154] within overdentures in the oral cavity of patients.…”
Section: Mechanotransduction To the Core: Yap/taz In The Periodontiummentioning
confidence: 98%
“…CDK1-cyclin B, also known as cell division control protein kinase 2-cyclin B (cdc2-cyclin B) functions at the G2/M phase of the cell cycle, to accelerate cell mitosis ( 60 ). SMFs (200 ± 60 mT, 48 ± 4 h) induced human malignant glioblastomata, such as U87 and U251, to arrest the G2/M phase by downregulating the expressions of cyclin B1 and CDK1 ( 61 ). The p53 protein is a critical participant in the signal transduction pathway which mediated apoptosis and G1 cell cycle arrest in mammalian cells ( 62 ).…”
Section: The Effects Of Mfs On Cell Proliferation Cell Cycle Arrestmentioning
confidence: 99%